Under the Corporate Radar: Examining Insider Business Cybercrime Victimization through an Application of Routine Activities Theory. Issue 9 (2nd September 2019) - Williams, Matthew L.; Levi, Michael; Burnap, Pete; Gundur, R.V.
ABSTRACT: Cybercrime is recognized as one of the top threats to UK economic security. On a daily basis, the computer networks of businesses suffer security breaches. A less explored dimension of this problem is cybercrimes committed by insiders. This paper provides a criminological analysis of corporate insider victimization. It begins by presenting reviews of insider criminal threats and routine activities theory as applied to cybercrime. Analysis of the nationally representative Cardiff University UK Business Cybercrime Survey then informs statistical models that predict the likelihood of businesses suffering insider cyber victimization, using routine activities and guardianship measures as predictors.